'In the end, you can only slag people off for so long': employee cynicism through work blogging. (17th March 2013) - Richards, James; Kosmala, Katarzyna
<x xml:space="preserve">Abstract</x> The paper critiques the ideology perspective of employee cynicism, which emphasises imaginary power and the employee's dependency on corporate culture initiatives. In contrast to the ideology perspective, this study draws on the narratives of work blogs and interviews with bloggers to suggest that being cynical about work can also give an employee a sense of control and attachment to their own occupational or professional community, while providing distance from corporate culture initiatives. The paper concludes with suggestions for future research about employee cynicism and the expanding possibilities researching cyberspace, which increasingly appears to be utilised by employees.